A Comparison of V/f and Field Oriented Control of Three Phase Induction Motors Employed in Load Sharing - Nayak, Roopa; Pallavi, Andhe (International Journal of Computer Sciences and Engineering, 2025)
There are various applications in industries where it has become essential to employ multiple motors to drive a common load. This necessity of multiple motor employment has aroused due to several reasons such as the presence of large loads, lack of space for a large motor, need for redundancy and process requirements. Also, there are some of the processes such as conveyor belt and mills which cannot operate with merely one motor. Any process that necessitates the employment of multiple motors to drive a common load will have to adopt load sharing arrangement which is essentially the usage of multiple motor- drive set. With the advancements that has happened in Power Electronics and Electric Drive streams, the user has a wide range of motors and drives to choose from, for load sharing. However, a study of behavior of these motors and drives when employed for load sharing is of utmost importance, as this helps the user to choose the appropriate motor -drive set for the required application. Induction motors are used in majority of the applications in industry. Scalar control and vector control are adopted for induction motor control. Understanding the behavior of induction motor under scalar and vector control in a load sharing arrangement will ease the selection of appropriate control strategy. Therefore, a comparative study of V/f and Field Oriented Control strategies for controlling induction motor in a load sharing arrangement is carried out and results are discusse.